Constrained large-eddy simulation of laminar-turbulent transition in compressible channel flows - Sanmu Chen; Zhou Jiang; Minping Wan; Shiyi Chen (Advances in Aerodynamics, 2023)
Abstract An improved approach for constrained large-eddy simulations (CLES) of wall-bounded compressible transitional flows is proposed by introducing an intermittency factor. The improved model is tested and validated with compressible channel flows at various Mach numbers and Reynolds numbers that are transitioning from laminar to turbulent states. The improved model is compared against traditional dynamic Smagorinsky model (DSM) and Direct Numerical Simulations (DNS), where the improved model is in better agreement with DNS results than traditional DSM model, in terms of mean velocity profiles, total Reynolds stress and total heat flux. Therefore, the proposed method can be used to accurately predict the temporal laminar-turbulent transition process of compressible wall-bounded flows.